Frequency of human papilloma virus (HPV) vaccination among female health care providers and reasons for non-immunization at a public sector hospital - Muhammad Hamza Shafiq; Mansoor, Misha; Arshad, Azal; Mansoor, Shanzay; Sana Iftikhar (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the knowledge and attitude of female healthcare providers about human papilloma virus and its vaccination, to determine the frequency of respondents vaccinated against the virus, and to evaluate the reasons for non-immunisation. Method: The cross-sectional study was conducted at the Jinnah Hospital, Lahore, Pakistan, from January 7 to February 20, 2022, and comprised female health care providers aged 20-60 years. Data was collected using a self-assessing questionnaire. Data was analysed using SPSS 22. Results: Of the 250 individuals approached, 210(84%) took part in the study. The mean age was 28.9+/-7.99 years. Most of the subjects were house officers, medical officers or senior registrars 138(65.7%), and 126(60%) were unmarried. Overall, 170(81%) respondents knew about human papilloma virus and 174(82.9%) were aware of its link with cervical cancer. Even though 128(61%) respondents knew that the virus can be prevented by vaccine, 14(6.7%) were actually vaccinated. The vaccinated individuals had better knowledge about HPV, its spread, complications, its association with cervical cancer, prevention by vaccination and availability of vaccine compared to the non-vaccinated (p =0.05) Conclusion: The trend of human papilloma virus vaccination among female health professionals was found to be low, and lack of awareness and counselling was the leading cause. Key Words: Human papillomavirus, Cervical cancer, Vaccination.